Chronic chlorpyrifos exposure induces oxidative stress, apoptosis and immune dysfunction in largemouth bass (Micropterus salmoides). (1st August 2021) - Zhao, Liulan; Tang, Gang; Xiong, Chen; Han, Shuaishuai; Yang, Chunping; He, Kuo; Liu, Qiao; Luo, Jie; Luo, Wei; Wang, Yan; Li, Zhiqiong; Yang, Song
Abstract: This study was undertaken to (a) evaluate the destructive effects of chronic exposure to low-dose of chlorpyrifos (CPF) on antioxidant system and immune function in largemouth bass ( Micropterus salmoides ), and (b) to examine whether dietary supplementation of curcumin can mitigate the adverse effects induced by CPF contamination. The experiment consisted of three groups (with three replicates, 30 fish per replicate) which lasted for 60 days: A control group (without CPF exposure or CU application), CP group (exposed to 0.004 mg/L of CPF), and CU group (exposed to 0.004 mg/L of CPF and fed a diet containing 100 mg curcumin per kg feed). The results showed that CPF contamination leads to reduced weight gain, severe histopathological lesions, decreased activity of antioxidant enzymes and down-regulated expression of antioxidant-related genes. Moreover, CPF upregulated the expression of pro-inflammatory genes such as TNF-α, IL-8, IL-15, downregulated anti-inflammatory genes TGF-β1, IL-10, and promoted apoptosis through overexpression of Caspase-3, Caspase-8, caspase-9 and Bax . In addition, curcumin supplementation showed significant improvement in oxidative stress, apoptosis and immune dysfunction, but the improved effect gradually weakened during the exposure last. Gas chromatography-mass spectrometry (GC-MS) analysis for accumulation of CPF in muscle supported the changes of general physiological structure, excessive apoptotic responses, abnormal antioxidant and immune system functions and posed potential human health risks to children based on target hazard quotient. These results suggested that chronic exposure to CPF can cause oxidative stress, apoptosis and immune dysfunction, and that curcumin have the potential to reduce pesticides residues in fish. This also highlights the importance of monitoring pesticides residues in aquatic products and aquaculture aquatic environments. Graphical abstract: Image 1 Highlights: Chlorpyrifos exposure could cause oxidative stress, promote apoptosis and inflammation in gill, gut and liver. Chronic chlorpyrifos led to the accumulation of Chlorpyrifos in muscle of fish. Curcumin significantly alleviated the adverse damage caused by chlorpyrifos within a certain period of time. Chlorpyrifos bioaccumulation might hinder the healthy farming of largemouth bass. Chlorpyrifos residues cause potential human health risks, especially for children.